Model Peningkatkan Kepuasan Dan Loyalitas Nasabah Yang Berbasis Sistem Aplikasi Dan Kualitas Pelayanan Pada Bri Wilayah Kabupaten Ngawi - Siti Fatonah; Lukman Ahmad Imron Pahlawi; Intan Arlita (ProBank, 2026)
This study aims to determine, test, and analyze strategies for increasing customer satisfaction and loyalty through application system and service quality aspects at BRI Ngawi Branch Office. The researcher took a sample of 100 respondents. The sampling technique used Convenience Sampling. The results of the study indicate that the application system has a significant effect on customer decisions. Service quality has a significant effect on customer decisions. The application system has an insignificant effect on customer loyalty. Service quality has a significant effect on customer loyalty. Customer decisions have a significant effect on customer loyalty. The results of the F test can be concluded that together the application system, service quality, and customer decisions have a significant effect on customer loyalty at BRI Ngawi Branch Office. The total R2 value of 0.775 can be interpreted that the variation in customer loyalty at BRI Ngawi Branch Office is explained by the application system, service quality, and customer decisions variables, amounting to 77.5% and the remaining 22.5% is explained by other variables outside the research model, for example, service procedures and product quality. Conclusion of the path analysis: The application system is more effective through the indirect path, because the results of the indirect effect are greater than the direct effect. Service quality is more effective through the direct path, because the results of the direct effect are greater than the indirect effect.